In vitro differentiation of conjunctiva mesenchymal stem cells into insulin producing cells on natural and synthetic electrospun scaffolds. (November 2019) - Barati, Ghasem; rahmani, Ali; Nadri, Samad
Abstract: Polymers are used in tissue engineering as a scaffold. In this study the differentiation capability of conjunctiva mesenchymal stem cells (CJMSCs) on natural and synthetic nanofibrous electrospun scaffolds into insulin producing cells (IPCs) were studied. Natural Silk fibroin and synthetic PLLA polymers were used to fabricate electrospun scaffolds. These scaffolds are characterized by SEM and CJMSCs were differentiated into IPCs on these scaffolds. The differentiation efficiency was measured by analysis the expression of specific pancreatic markers by RT-qPCR and insulin release capacity via ELISA. Microscopy analysis showed the fabrication of uniform nanofibers and the formation of the islet-like clusters at the end of differentiation period. Significant differences in expression of Pdx-1 and glucagon were observed in PLLA scaffold compared to Silk scaffold (Fold: 1.625 and 1.434, respectively; P-value ≤ 0.0001 for both). Furthermore, insulin secretion at high glucose concentration was significantly higher in cells differentiated on PLLA scaffold than those cultured on Silk scaffold (P-value: 0.012). The scaffolds can enhance the differentiation of IPCs from CJMSCs. In this way, PLLA synthetic scaffold was more efficient than Silk natural scaffold. We conclude that the nanoﬁbrous scaffolds reported herein could be used as a potential supportive matrix for islet tissue engineering. Highlights: IPCs differentiation of CJMSCs on Silk, PLLA scaffolds. PLLA enhance IPCs differentiation of CJMSCs. High secretion of insulin in PLLA scaffold.